Solid electrolyte composite membrane, preparation method thereof and solid-state battery

Ultrasonic induces polymer electrolyte cross-linking and polymerization and forms chemical bonds with surface hydroxylated oxide electrolytes, solving the problems of low ionic conductivity, chemical stability and mechanical strength of electrolytes in solid-state batteries, and realizing the preparation of high-performance solid-state batteries.

CN119400934APending Publication Date: 2025-02-07SVOLT ENERGY TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411517991.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The polymer electrolytes of existing solid-state batteries have low ionic conductivity, low chemical stability, insufficient mechanical strength, poor interfacial compatibility of oxide electrolytes, poor flexibility and processability, which limits the widespread application of solid-state batteries.

Method used

Ultrasonic initiates cross-linking and polymerization of polymer electrolyte monomers and forms chemical bonds with the surface hydroxylated oxide solid electrolyte to improve interface compatibility. At the same time, plasma-modified oxide solid electrolyte surface is used to improve its processability and flexibility .

Benefits of technology

The ionic conductivity, chemical stability and mechanical strength of the solid-state electrolyte composite film are improved, the interface compatibility with the electrode material is improved, and the power density, charge and discharge rate, cycle performance and safety performance of the solid-state battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119400934A_ABST
    Figure CN119400934A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of solid-state batteries, in particular to a solid-state electrolyte composite membrane, a preparation method thereof and a solid-state battery. The preparation method comprises the following steps: performing ultrasonic-initiated cross-linking polymerization on a polymer solid electrolyte monomer, a cross-linking agent and a surface hydroxylated oxide solid electrolyte to obtain a polymer-oxide solid electrolyte matrix, washing the polymer-oxide solid electrolyte matrix, and soaking the polymer-oxide solid electrolyte matrix in an electrolyte to obtain the solid electrolyte composite membrane. According to the invention, crosslinking of the polymer electrolyte monomer is initiated by ultrasound, and chemical bonds are formed between part of the polymer electrolyte monomer and the surface-hydroxylated oxide solid electrolyte, so that the interfacial compatibility of the polymer electrolyte monomer and the surface-hydroxylated oxide solid electrolyte is effectively improved, and the ionic conductivity, chemical stability and mechanical strength of the polymer electrolyte are improved; due to the properties of easy processing, good flexibility and the like of the polymer electrolyte, the interface compatibility between the oxide solid electrolyte and the positive and negative pole pieces can be fully improved, the flexibility and the processability are improved, and a win-win effect is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid-state batteries, and in particular to a solid-state electrolyte composite membrane and a preparation method thereof, and a solid-state battery. Background Art

[0002] Solid-state battery technology is a hot area in the current battery industry. It has attracted much attention due to its advantages such as high energy density, high safety and long cycle life. Solid-state battery technology is mainly divided into three technical routes: polymer, oxide and sulfide. Sulfide solid electrolytes have attracted much attention due to their high conductivity, but they also face challenges such as high cost and poor stability. Oxide electrolytes excel in thermal stability, while polymer electrolytes have advantages in processing and interface compatibility.

[0003] However, the current polymer solid electrolytes have the following disadvantages: ① low ionic conductivity, which limits the power density and charge and discharge rate of the battery; ② low chemical stability, narrow electrochemical window, easy chemical decomposition at high voltage, affecting the battery's cycle and safety performance; ③ low mechanical strength, easy to break or deform during use. Oxide solid electrolytes have the following disadvantages: ① poor interface compatibility: generally single crystal materials, poor interface compatibility with electrode materials, high contact impedance, and require additional interface processing technology; ② poor flexibility and processability: oxide electrolytes are usually brittle and not easy to process into thin films or other flexible shapes. The above defects limit the further widespread application of solid-state batteries.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The first purpose of the present invention is to provide a method for preparing a solid electrolyte composite membrane, by inducing cross-linking of polymer electrolyte monomers through ultrasound, and forming chemical bonds between some polymer electrolyte monomers and surface hydroxylated oxide solid electrolytes, thereby effectively improving the interface compatibility between the two, and improving the ionic conductivity, chemical stability and mechanical strength of the polymer electrolyte. The easy processing and good flexibility of the polymer electrolyte can also fully improve the interface compatibility between the oxide solid electrolyte and the positive and negative electrode sheets, and improve flexibility and processability, thereby achieving a win-win effect and facilitating the widespread application of solid-state batteries.

[0006] The second purpose of the present invention is to provide a solid electrolyte composite membrane, which has high ionic conductivity, improves the power density and charge and discharge rate of the battery, has good chemical stability, broadens the electrochemical window of the battery, improves the cycle performance of the battery, has high mechanical strength, improves the service life and safety performance of the battery, has good interface compatibility with electrode materials, is easy to process, and has good flexibility.

[0007] The third object of the present invention is to provide a solid-state battery having high power density, fast charge and discharge rate, excellent cycle performance, good safety performance and broad application prospects.

[0008] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0009] The present invention first provides a method for preparing a solid electrolyte composite membrane, comprising the following steps: a polymer solid electrolyte monomer, a crosslinking agent and a surface hydroxylated oxide solid electrolyte undergo a crosslinking polymerization reaction under ultrasonic conditions, and a polymer-oxide solid electrolyte matrix is ​​obtained after the crosslinking polymerization reaction is completed; and the polymer-oxide solid electrolyte matrix is ​​washed and then soaked in an electrolyte to obtain the solid electrolyte composite membrane.

[0010] Furthermore, the mass ratio of the polymer solid electrolyte monomer to the cross-linking agent is 1:0.05-0.3.

[0011] Furthermore, the mass ratio of the surface hydroxylated oxide solid electrolyte to the polymer solid electrolyte monomer is 0.5 to 2:1.

[0012] Furthermore, the method for preparing the surface hydroxylated oxide solid electrolyte comprises: during the process of airflow pulverization of the oxide solid electrolyte, introducing plasma containing hydrogen and / or oxygen elements to obtain the surface hydroxylated oxide solid electrolyte.

[0013] Furthermore, the flow rate of the plasma accounts for 30% to 80% of the air flow rate.

[0014] Furthermore, the plasma includes at least one of air plasma, water plasma, and oxygen and hydrogen mixed plasma.

[0015] Furthermore, the oxide solid electrolyte includes at least one of a perovskite structure solid electrolyte, a garnet structure solid electrolyte and a spinel structure oxide solid electrolyte.

[0016] Furthermore, the polymer solid electrolyte in the solid electrolyte composite membrane includes at least one of a polyethylene oxide-based electrolyte, a polyacrylonitrile-based electrolyte, a polymethyl methacrylate-based electrolyte, a polyvinylidene fluoride-based electrolyte, a polycarbonate-based electrolyte, a polysiloxane-based electrolyte, a polyimide-based electrolyte, a polyetheretherketone-based electrolyte, a polyphosphate-based electrolyte and a polyester-based electrolyte.

[0017] Further, the polymer solid electrolyte monomer includes at least one of ethylene oxide, acrylonitrile, acrylic acid, methyl methacrylate, vinylidene fluoride, siloxane, ethylene glycol and lactic acid; or, the polymer solid electrolyte monomer includes at least one of a combination of dianhydride and diamine, a combination of biphenyl dianhydride and diaminodiphenylmethane, a combination of polycarboxylic acid and polyol, a combination of butylene terephthalate and neopentyl glycol, and a combination of hydroquinone and para-fluorobenzophenone.

[0018] Furthermore, the cross-linking agent includes at least one of cumene peroxide, methylene bisacrylamide and diethylenetriamine.

[0019] Furthermore, the lithium salt in the electrolyte includes at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(trifluoromethylsulfonyl)imide, lithium trifluoromethanesulfonate, lithium bis(oxalatoborate), lithium difluorooxalatoborate and dicyanotriazole lithium salt.

[0020] Furthermore, the solvent in the electrolyte includes at least one of ethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, propylene carbonate, 1,2-dimethoxypropane, dimethoxymethane and ethylene glycol dimethyl ether.

[0021] Furthermore, the washing method comprises: using an organic solvent to immerse and wash the polymer-oxide solid electrolyte matrix.

[0022] Furthermore, after the electrolyte soaking, a cutting step is also included.

[0023] The present invention further provides a solid electrolyte composite membrane prepared according to the preparation method of the solid electrolyte composite membrane.

[0024] Furthermore, the thickness of the solid electrolyte composite membrane is 10 to 20 μm.

[0025] Furthermore, the ionic conductivity of the solid electrolyte composite membrane is ≥10×10 -6 S cm -1 .

[0026] The present invention also provides a solid-state battery, comprising the solid-state electrolyte composite membrane.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] (1) The preparation method of the solid electrolyte composite membrane provided by the present invention is to initiate the cross-linking polymerization of the polymer electrolyte monomers by ultrasound. During this process, chemical bonds are formed between some of the polymer electrolyte monomers and the surface hydroxylated oxide solid electrolyte, which effectively improves the interface compatibility between the two and improves the ionic conductivity, chemical stability and mechanical strength of the polymer electrolyte. The easy processing and good flexibility of the polymer electrolyte can also fully improve the interface compatibility between the oxide solid electrolyte and the positive and negative electrode sheets, and improve flexibility and processability, thereby achieving a win-win effect.

[0029] (2) The preparation method of the solid electrolyte composite membrane provided by the present invention adopts a surface hydroxylated oxide solid electrolyte, which can make the polymer and the oxide combine more tightly, reduce the impedance increase caused by the interface, inhibit the contact deterioration caused by the volume change of the oxide solid electrolyte during the cycle, and at the same time expand the voltage window and chemical stability of the polymer solid electrolyte.

[0030] (3) The preparation method of the solid electrolyte composite membrane provided by the present invention adopts plasma to modify the surface of the oxide solid electrolyte, and simultaneously performs surface modification during the post-treatment process of the oxide solid electrolyte preparation to increase hydroxyl groups. There is no need for major production line transformation and equipment investment, the processing cost remains almost unchanged, and the amount of surface hydroxyl groups is controllable.

[0031] (4) The preparation method of the solid electrolyte composite membrane provided by the present invention adopts ultrasound-assisted synthesis of polymer solid electrolyte, which has high synthesis efficiency and fast polymerization speed, can effectively reduce the problem of uneven composite caused by the precipitation of oxide solid electrolyte, and improve the performance stability of the composite membrane.

[0032] (5) The solid electrolyte composite membrane prepared by the preparation method of the solid electrolyte composite membrane provided by the present invention has both the processability and flexibility of the polymer and the high ionic conductivity, mechanical strength and chemical stability of the oxide, and is convenient for battery cell processing and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0034] Figure 1 This is a process flow chart for preparing a solid electrolyte composite membrane according to Example 1 provided by the present invention. DETAILED DESCRIPTION

[0035] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0036] If there is no special explanation, in the present invention, "the first aspect", "the second aspect", "the third aspect", "the fourth aspect", etc. are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "the first", "the second", "the third", "the fourth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.

[0037] If there is no special explanation, the "include" and "comprising" mentioned in the present invention represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0038] If there is no special explanation, in the present invention, "one or more" or "at least one" refers to any one, any two or more of the listed items. Among them, "several" refers to any two or more of the listed items.

[0039] In a first aspect, the present invention provides a method for preparing a solid electrolyte composite membrane, namely a polymer-oxide composite solid electrolyte membrane, comprising the following steps:

[0040] Under ultrasonic conditions, a polymer solid electrolyte monomer, a crosslinking agent and a surface hydroxylated oxide solid electrolyte undergo crosslinking polymerization reaction, and after the crosslinking polymerization reaction is completed, a polymer-oxide solid electrolyte matrix is ​​obtained.

[0041] Among them, ultrasound-assisted synthesis of polymer solid electrolytes and synchronous composite oxide solid electrolytes can improve the interfacial compatibility between polymers and oxides.

[0042] After the surface of the oxide solid electrolyte is modified with hydroxyl groups, a covalent bond can be formed between it and the polymer solid electrolyte, making the bond tighter and effectively improving the contact degradation caused by the difference in volume change rate during the cycle.

[0043] The polymer-oxide solid electrolyte matrix is ​​washed, and the purpose of soaking and washing is to remove the unreacted polymer solid electrolyte monomer and cross-linking agent. Then, the electrolyte is soaked to replace the solvent used for washing, and part of the electrolyte remains in the solid electrolyte composite membrane, so as to obtain the solid electrolyte composite membrane. The polymer-oxide composite solid electrolyte is directly formed into a film, which is convenient for battery processing and application.

[0044] The preparation method of the solid electrolyte composite membrane provided by the present invention is based on the respective advantages of polymer solid electrolyte and oxide solid electrolyte. The two materials are combined during the synthesis process of the polymer solid electrolyte to give full play to their respective strengths, thereby improving the application scenarios of the solid electrolyte composite membrane and solid-state batteries.

[0045] Specifically, the present invention initiates cross-linking polymerization of polymer electrolyte monomers through ultrasound. During this process, chemical bonds are formed between some polymer electrolyte monomers and surface hydroxylated oxide solid electrolytes, which effectively improves the interfacial compatibility between the two and improves the ionic conductivity, chemical stability and mechanical strength of the polymer electrolyte. The easy processing and good flexibility of the polymer electrolyte can also fully improve the interfacial compatibility between the oxide solid electrolyte and the positive and negative electrode sheets, and improve flexibility and processability, thereby achieving a win-win effect.

[0046] Among them, the use of surface hydroxylated oxide solid electrolytes can make the polymer and oxide combine more tightly, reduce the impedance increase caused by the interface, inhibit the contact deterioration caused by the volume change of the oxide solid electrolyte during the cycle, and at the same time expand the voltage window and chemical stability of the polymer solid electrolyte.

[0047] In addition, ultrasound-assisted synthesis of polymer solid electrolytes has high synthesis efficiency and fast polymerization speed, which can effectively reduce the problem of uneven composite caused by the sedimentation of oxide solid electrolytes and improve the performance stability of the composite membrane.

[0048] In some specific embodiments, the method of initiating a cross-linking polymerization reaction by ultrasound is as follows: a polymer solid electrolyte monomer and a cross-linking agent are added to a temperature-controlled container, the temperature is controlled at 20 to 30°C (e.g., room temperature 25°C), and after sufficient dispersion by mechanical stirring, a surface hydroxylated oxide solid electrolyte is added thereto, and stirring and dispersion are continued for a period of time, and then stirring is stopped, ultrasound is turned on to initiate polymerization, and the solution is solidified to obtain a polymer-oxide solid electrolyte matrix.

[0049] It is understandable that the ultrasonic conditions are related to the volume of the container and can be set as needed according to the volume of the container.

[0050] In some specific embodiments, in order to further improve the interface compatibility, flexibility and processing performance of the solid electrolyte composite membrane, the mass ratio of the polymer solid electrolyte monomer to the cross-linking agent is 1:0.05-0.3; including but not limited to any one of 1:0.05, 1:0.08, 1:0.1, 1:0.13, 1:0.15, 1:0.18, 1:0.2, 1:0.22, 1:0.25, 1:0.27, 1:0.3 or the range value between any two of them.

[0051] In some specific embodiments, in order to further improve the comprehensive performance of the solid electrolyte composite membrane, such as ionic conductivity, chemical stability, mechanical strength, interface compatibility with positive and negative electrode sheets, flexibility and processability, the mass ratio of the surface hydroxylated oxide solid electrolyte and the polymer solid electrolyte monomer is 0.5 to 2:1, including but not limited to any one of 0.5:1, 0.7:1, 1:1, 1.3:1, 1.5:1, 1.8:1, 2:1 or a range between any two of them.

[0052] In some specific embodiments, the method for preparing the surface hydroxylated oxide solid electrolyte includes: introducing a plasma containing hydrogen and / or oxygen elements during airflow pulverization of the oxide solid electrolyte, performing surface physical etching and surface modification on the oxide solid electrolyte to introduce hydroxyl groups, and obtaining the surface hydroxylated oxide solid electrolyte.

[0053] The present invention performs surface group modification during the post-production treatment of the oxide solid electrolyte. The material is modified by introducing plasma during the pulverization of the oxide solid electrolyte. There is no need to carry out large-scale equipment and production line transformation, and the initial investment and transformation cost are low. The hydroxyl content on the surface of the material is stable and controllable. The surface hydroxyl content can be flexibly adjusted according to the addition ratio of the oxide solid electrolyte in combination with the subsequent polymer electrolyte synthesis process.

[0054] In some specific embodiments, in order to further improve the ionic conductivity, chemical stability and mechanical strength of the solid electrolyte composite membrane, the flow rate of the plasma accounts for 30% to 80% of the air flow rate used for airflow crushing; including but not limited to any point value of 30%, 40%, 50%, 60%, 70%, 80% or any range value between two of them.

[0055] In some specific embodiments, the plasma includes at least one of air plasma, water plasma, and oxygen and hydrogen mixed plasma.

[0056] In some specific embodiments, the oxide solid electrolyte includes at least one of a perovskite structure solid electrolyte, a garnet structure solid electrolyte, and a spinel structure oxide solid electrolyte.

[0057] As an example, the perovskite structure solid electrolyte includes, for example, lanthanum gallium oxide (LaGaO3), strontium titanate (SrTiO3), etc.; the garnet structure solid electrolyte includes, for example, lithium aluminum titanium phosphate (LATP), lithium lanthanum zirconium oxide (LLZO), lithium lanthanum titanium oxide (LLTO), lithium titanium zirconium oxide (LZTO), lithium lanthanum titanium zirconium oxide (LLZTO), etc.; the spinel structure oxide solid electrolyte includes, for example, lithium manganese oxide (LiMnO4), etc., but is not limited to this.

[0058] In some specific embodiments, the polymer solid electrolyte monomer includes at least one of self-polymerizable monomers such as ethylene oxide, acrylonitrile, acrylic acid, methyl methacrylate, vinylidene fluoride, siloxane, ethylene glycol and lactic acid; or a combination of dianhydride + diamine (such as phthalic anhydride + p-phenylenediamine), biphenyl dianhydride + diaminodiphenylmethane, polycarboxylic acid + polyol (such as terephthalic acid + ethylene glycol), butylene terephthalate + neopentyl glycol, hydroquinone + para-fluorobenzophenone, etc.

[0059] In some specific embodiments, the cross-linking agent is at least one of cumene peroxide, methylene bisacrylamide and diethylenetriamine.

[0060] In some specific embodiments, the polymer solid electrolyte in the solid electrolyte composite membrane includes polyethylene oxide (PEO) based electrolyte, polyacrylonitrile (PAN) based electrolyte, polymethyl methacrylate (PMMA) based electrolyte, polyvinylidene fluoride (PVDF) based electrolyte, polycarbonate (PC) based electrolyte, polysiloxane (PDMS) based electrolyte, polyimide (PI) based electrolyte, polyetheretherketone (PEEK) based electrolyte, polyphosphate (PPE) based electrolyte, polyester based electrolyte: such as polylactic acid (PLA), polyethylene glycol (PEG), etc., but not limited to these.

[0061] In some specific embodiments, the lithium salt in the electrolyte includes at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTf), lithium bis(oxalatoborate) (LiBOB), lithium difluorooxalatoborate (LiDFOB) and lithium dicyanotriazole (LiDCTA).

[0062] In some specific embodiments, the solvent in the electrolyte includes at least one of ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), propylene carbonate (PC), 1,2-dimethoxypropane (DMP), dimethoxymethane (DMM) and ethylene glycol dimethyl ether (DME).

[0063] As an example, the electrolyte may be a solution with EC as a solvent and a lithium salt concentration of 1 mol / L.

[0064] In some specific embodiments, the washing method includes: immersing and washing the polymer-oxide solid electrolyte matrix with an organic solvent. The organic solvent can be any reagent commonly used in the art, such as NMP (N-methyl-2-pyrrolidone), but is not limited thereto. The immersion washing is performed no less than 2 times.

[0065] In some other specific embodiments, the polymer-oxide solid electrolyte matrix can also be soaked and washed with an electrolyte, but this is costly. Therefore, it is preferred to use an organic solvent such as NMP for washing to remove unreacted polymer solid electrolyte monomers and crosslinking agents to reduce production costs.

[0066] In some specific embodiments, the number of times of using electrolyte immersion to replace the solvent used for washing is not less than two times.

[0067] In some specific embodiments, after the electrolyte is soaked, the step of cutting into a target shape and a target thickness is also included. Directly processing into a film by cutting is simple and has a short process, which can make the processing of solid-state lithium batteries as convenient as traditional liquid lithium-ion batteries, greatly reduce processing costs, and improve production line yield.

[0068] In a second aspect, the present invention provides a solid electrolyte composite membrane prepared by the method for preparing the solid electrolyte composite membrane.

[0069] The solid electrolyte composite membrane has the advantages of high ionic conductivity, improved battery power density and charge and discharge rate, good chemical stability, broadened battery electrochemical window, improved battery cycle performance, high mechanical strength, improved battery service life and safety performance, good interface compatibility with electrode materials, easy processing and good flexibility.

[0070] In some specific embodiments, the thickness of the solid electrolyte composite membrane is 10 to 20 μm, including but not limited to any point value of 10 μm, 12 μm, 15 μm, 18 μm, 20 μm, or a range value between any two of them.

[0071] In some specific embodiments, the ionic conductivity of the solid electrolyte composite membrane is ≥10×10 -6 S cm -1 , including but not limited to 10×10 -6 S cm -1 , 20×10 -6 S cm -1 ,30×10 -6 S cm -1 , 40×10 -6 S cm -1 , 50×10 -6 S cm -1 , 60×10 -6 S cm -1 70×10 -6 S cm -1 ,80×10 -6 S cm -1 ,90×10 -6 S cm -1 , 100×10 -6 S cm -1 , 110×10 -6 S cm -1 , 120×10 -6 S cm -1 , 130×10 -6 S cm -1 , 150×10 -6 S cm -1 , 200×10 -6 S cm -1 ,300×10 -6 S cm -1 , 400×10 -6 S cm -1 , 500×10 -6 S cm -1 , 600×10 -6 S cm -1 ,800×10 -6 S cm -1 , 1000×10 -6 S cm -1 The solid electrolyte composite membrane provided by the present invention has high ion conductivity.

[0072] In some specific embodiments, the ionic conductivity of the solid electrolyte composite membrane after 400 cycles at room temperature is ≥4×10 -6 S cm -1 , including but not limited to 4×10-6 S cm -1 , 5×10 -6 S cm -1 , 8×10 -6 S cm -1 , 10×10 -6 S cm -1 , 20×10 -6 S cm -1 ,30×10 -6 S cm -1 , 40×10 -6 S cm -1 , 50×10 -6 S cm -1 , 60×10 - 6 S cm -1 70×10 -6 S cm -1 ,80×10 -6 S cm -1 ,90×10 -6 S cm -1 , 100×10 -6 S cm -1 , 110×10 - 6 S cm -1 , 120×10 -6 S cm -1 , 130×10 -6 S cm -1 , 150×10 -6 S cm -1 , 200×10 -6 S cm -1 ,300×10 -6 S cm -1 , 400×10 -6 S cm -1 , 500×10 -6 S cm -1 , 600×10 -6 S cm -1 ,800×10 -6 S cm -1 , 1000×10 -6 S cm -1 The solid electrolyte composite membrane provided by the present invention has high chemical stability.

[0073] In a third aspect, the present invention provides a solid-state battery comprising the solid-state electrolyte composite membrane.

[0074] This solid-state battery has high power density, fast charge and discharge rate, excellent cycle performance, good safety performance and broad application prospects.

[0075] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0076] Example 1

[0077] The method for preparing the solid electrolyte composite membrane provided in this embodiment comprises the following steps:

[0078] (1) Surface treatment: During the air flow pulverization process of lithium lanthanum zirconium oxide (LLZO), H2O plasma accounting for 60% of the air flow was introduced to obtain surface hydroxylated LLZO.

[0079] (2) Ultrasonic-assisted synthesis: Methyl methacrylate (MMA) (polymer solid electrolyte monomer) and cross-linking agent methylene bisacrylamide are added to a temperature-controlled container in a mass ratio of 1:0.1, and the temperature is controlled at 25°C. After mechanical stirring to fully disperse, the surface hydroxylated LLZO obtained in step (1) is added thereto, wherein the mass ratio of the surface hydroxylated LLZO to the monomer is 1:1. Stirring and dispersing is continued for 0.5 h, and then stirring is stopped. Ultrasonic induction cross-linking polymerization is started, and the solution is solidified to obtain a polymer (polymethyl methacrylate PMMA)-oxide (LLZO) solid electrolyte matrix.

[0080] (3) Preparation of composite membrane: The substrate obtained in step (2) was washed by immersion in NMP for 3 times to remove unreacted monomers and cross-linking agents, and then immersed in an electrolyte solution with EC as solvent and lithium salt LiPF6 concentration of 1 mol / L for 2 times, and then cut to obtain a solid electrolyte composite membrane with a thickness of 15 μm.

[0081] like Figure 1 FIG. 2 is a process flow chart of the method for preparing the solid electrolyte composite membrane provided in this embodiment. Figure 1As shown, in the post-processing stage of the oxide solid electrolyte crushing, a plasma flow is introduced through a dry compressed air intake pipe, and the surface of the material is physically etched and modified to introduce hydroxyl groups during the air flow crushing process. Then, the polymer electrolyte is synthesized by ultrasound-assisted method, and the surface-modified oxide solid electrolyte is added before the polymerization reaction is initiated, and the polymerization is initiated after sufficient dispersion. After the polymerization is completed, the obtained material is washed and the solvent is replaced, and then processed into a membrane, that is, a polymer-oxide composite solid electrolyte membrane is obtained.

[0082] Example 2

[0083] The method for preparing the solid electrolyte composite membrane provided in this embodiment is basically the same as that in Embodiment 1, except that H2O plasma accounting for 30% of the air flow rate is introduced in step (1).

[0084] Example 3

[0085] The method for preparing the solid electrolyte composite membrane provided in this embodiment is basically the same as that in Embodiment 1, except that H2O plasma accounting for 80% of the air flow rate is introduced in step (1).

[0086] Example 4

[0087] The method for preparing the solid electrolyte composite membrane provided in this embodiment is substantially the same as that in embodiment 1, except that in step (2), the mass ratio of the surface hydroxylated LLZO to the monomer is 2:1.

[0088] Example 5

[0089] The method for preparing the solid electrolyte composite membrane provided in this embodiment is substantially the same as that in embodiment 1, except that in step (2), the mass ratio of the surface hydroxylated LLZO to the monomer is 0.5:1.

[0090] Example 6

[0091] The method for preparing the solid electrolyte composite membrane provided in this embodiment is basically the same as that in Embodiment 1, except that in step (1), the H2O plasma is replaced by an air plasma of an equal flow rate.

[0092] Example 7

[0093] The method for preparing the solid electrolyte composite membrane provided in this embodiment is basically the same as that in Embodiment 1, except that in step (1), lithium lanthanum zirconium oxide is replaced by lithium manganate.

[0094] Example 8

[0095] The method for preparing the solid electrolyte composite membrane provided in this embodiment is basically the same as that in Embodiment 1, except that in step (1), lithium lanthanum zirconium oxide is replaced by Li2ZrO3.

[0096] Example 9

[0097] The preparation method of the solid electrolyte composite membrane provided in this embodiment is basically the same as that in embodiment 1, except that in step (2), the monomer is replaced by ethylene oxide, and the cross-linking agent is replaced by cumene peroxide. The polymer solid electrolyte in the solid electrolyte composite membrane prepared in this embodiment is a polyethylene oxide-based electrolyte.

[0098] Example 10

[0099] The method for preparing the solid electrolyte composite membrane provided in this embodiment is basically the same as that in Embodiment 1, except that the mass ratio of the monomer to the cross-linking agent in step (2) is 1:0.3.

[0100] Embodiment 11

[0101] The preparation method of the solid electrolyte composite membrane provided in this embodiment is basically the same as that in embodiment 1, except that in step (3), an electrolyte solution with DMC as solvent and LiBOB concentration of 1.5 mol / L is used for immersion and replacement three times.

[0102] Comparative Example 1

[0103] The preparation method of the solid electrolyte composite membrane provided in this comparative example is basically the same as that of Example 1, except that step (1) is not performed, and surface hydroxylated LLZO is not added in step (2).

[0104] Comparative Example 2

[0105] The surface hydroxylated LLZO prepared in Example 1 was used to prepare an oxide solid electrolyte membrane with the same thickness as in Example 1 according to the following method: according to the mass ratio of surface hydroxylated LLZO:PVDF=98:2, using NMP as solvent, and aiming at a solid content of 80%, the mixture was fully mixed under mechanical stirring, and the mixture was coated on the positive electrode sheet with a controlled thickness of 15 μm after drying. After drying, the oxide solid electrolyte membrane was obtained.

[0106] Comparative Example 3

[0107] The preparation method of the oxide solid electrolyte membrane provided in this comparative example is basically the same as that of comparative example 2, except that the surface hydroxylated LLZO is replaced by LLZO (not surface hydroxylated).

[0108] Comparative Example 4

[0109] The preparation method of the solid electrolyte composite membrane provided in this comparative example is basically the same as that of Example 1, except that step (1) is not performed, and in step (2), the surface hydroxylated LLZO is replaced by an equal mass of unsurface treated LLZO.

[0110] Experimental example

[0111] The initial ionic conductivity of the solid electrolyte composite membranes prepared in each embodiment and each comparative example was measured by an ionic conductivity meter. The results are shown in Table 1.

[0112] Then, the solid electrolyte composite membranes were used to assemble single-chip batteries, which were cycled for 400 cycles at room temperature (test conditions: voltage window 2.5-4.5 V, charge and discharge rate 1 C / 1 C, temperature 25°C). After that, the ionic conductivity of each membrane was disassembled and tested (referred to as post-cycle ionic conductivity). The results are shown in Table 1.

[0113] Table 1 Initial ionic conductivity and ionic conductivity after cycling

[0114]

[0115]

[0116] According to Table 1, by comparing Example 1 and Comparative Example 1, it can be seen that the initial ionic conductivity of Example 1 is significantly improved compared with that of Comparative Example 1, which indicates that the composite oxide solid electrolyte has a significant effect on improving the ionic conductivity.

[0117] Comparing Example 1 and Example 3, it can be seen that the flow rate of plasma will affect the initial ionic conductivity of the solid electrolyte composite membrane.

[0118] Comparing Example 1 and Example 4, it can be seen that the ratio of surface hydroxylated LLZO to monomer will not only affect the initial ionic conductivity of the solid electrolyte composite membrane, but also affect the chemical stability of the solid electrolyte composite membrane. In Example 4, the amount of surface hydroxylated LLZO added is relatively large, and the interface contact will deteriorate faster during the cycle, that is, the chemical stability of the solid electrolyte composite membrane is poor.

[0119] Comparing Comparative Example 2 and Comparative Example 3, it can be seen that surface hydroxylation will reduce the initial ionic conductivity of the solid electrolyte composite membrane to a certain extent, but it is still at the same order of magnitude and has little effect. However, surface hydroxylation can increase the groups on the surface of the oxide solid electrolyte particles, which can bond with the monomer, thereby combining more closely with the polymer, reducing the impedance of the oxide-polymer interface, and improving the contact degradation caused by the difference in volume change during the cycle, thereby expanding the voltage window of the solid electrolyte membrane and improving its chemical stability.

[0120] After the polymer solid electrolyte is compounded with the oxide solid electrolyte, for the pure polymer solid electrolyte, its ionic conductivity and puncture resistance can be improved, which can significantly improve the application safety under extreme working conditions. For the pure oxide solid electrolyte, its processability can be improved, and the flexibility of the battery cell and the interface contact with the electrode can be enhanced.

[0121] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.

Claims

1. A method for preparing a solid electrolyte composite membrane, characterized in that: The steps include: A polymer solid electrolyte monomer, a crosslinking agent and a surface hydroxylated oxide solid electrolyte undergo a crosslinking polymerization reaction under ultrasonic conditions, and a polymer-oxide solid electrolyte matrix is ​​obtained after the crosslinking polymerization reaction is completed; The polymer-oxide solid electrolyte matrix is ​​washed and then soaked in an electrolyte to obtain the solid electrolyte composite membrane.

2. The method for preparing a solid electrolyte composite membrane according to claim 1, characterized in that: The mass ratio of the polymer solid electrolyte monomer to the cross-linking agent is 1:0.05-0.3; And / or, the mass ratio of the surface hydroxylated oxide solid electrolyte to the polymer solid electrolyte monomer is 0.5 to 2:

1.

3. The method for preparing a solid electrolyte composite membrane according to claim 1, characterized in that: The method for preparing the surface hydroxylated oxide solid electrolyte comprises: during the process of airflow pulverization of the oxide solid electrolyte, introducing plasma containing hydrogen and / or oxygen elements to obtain the surface hydroxylated oxide solid electrolyte.

4. The method for preparing a solid electrolyte composite membrane according to claim 3, characterized in that: At least one of the following conditions is met: (1) The flow rate of the plasma accounts for 30% to 80% of the air flow rate; (2) The plasma includes at least one of air plasma, water plasma, and oxygen and hydrogen mixed plasma; (3) The oxide solid electrolyte includes at least one of a perovskite structure solid electrolyte, a garnet structure solid electrolyte and a spinel structure oxide solid electrolyte.

5. The method for preparing a solid electrolyte composite membrane according to claim 1, characterized in that: At least one of the following conditions is met: (1) The polymer solid electrolyte in the solid electrolyte composite membrane includes at least one of a polyethylene oxide-based electrolyte, a polyacrylonitrile-based electrolyte, a polymethyl methacrylate-based electrolyte, a polyvinylidene fluoride-based electrolyte, a polycarbonate-based electrolyte, a polysiloxane-based electrolyte, a polyimide-based electrolyte, a polyetheretherketone-based electrolyte, a polyphosphate-based electrolyte, and a polyester-based electrolyte; (2) The polymer solid electrolyte monomer includes at least one of ethylene oxide, acrylonitrile, acrylic acid, methyl methacrylate, vinylidene fluoride, siloxane, ethylene glycol and lactic acid; or, the polymer solid electrolyte monomer includes at least one of a combination of dianhydride and diamine, a combination of biphenyl dianhydride and diaminodiphenylmethane, a combination of polycarboxylic acid and polyol, a combination of butylene terephthalate and neopentyl glycol, and a combination of hydroquinone and para-fluorobenzophenone; (3) The cross-linking agent includes at least one of cumene peroxide, methylene bisacrylamide and diethylenetriamine.

6. The method for preparing a solid electrolyte composite membrane according to claim 1, characterized in that: The lithium salt in the electrolyte includes at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(trifluoromethylsulfonyl)imide, lithium trifluoromethanesulfonate, lithium bis(oxalatoborate), lithium difluorooxalatoborate and dicyanotriazole lithium salt; And / or, the solvent in the electrolyte includes at least one of ethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, propylene carbonate, 1,2-dimethoxypropane, dimethoxymethane and ethylene glycol dimethyl ether.

7. The method for preparing a solid electrolyte composite membrane according to claim 1, characterized in that: At least one of the following conditions is met: (1) The washing method comprises: soaking and washing the polymer-oxide solid electrolyte matrix with an organic solvent; (2) After the electrolyte soaking, a cutting step is also included.

8. A solid electrolyte composite membrane obtained by the method for preparing a solid electrolyte composite membrane according to any one of claims 1 to 7.

9. The solid electrolyte composite membrane according to claim 8, characterized in that: At least one of the following conditions is met: (1) The thickness of the solid electrolyte composite membrane is 10 to 20 μm; (2) The ionic conductivity of the solid electrolyte composite membrane is ≥10×10 -6 S cm -1 .

10. A solid-state battery, characterized in that: Comprising the solid electrolyte composite membrane as claimed in claim 8.

Citation Information

Patent Citations

  • Method for preparing three-dimensional porous polymer electrolyte film

    CN103545548A

  • Preparation method of high-flexibility polymer solid-state electrolyte membrane and preparation method of lithium ion battery

    CN108448162A

  • Solid electrolyte membrane and manufacturing method thereof, solid-state battery and electric vehicle

    CN111435758A

  • Modified ceramic material as well as preparation method and application of composite electrolyte prepared from modified ceramic material

    CN114361572A

  • Sodium battery composite solid electrolyte and preparation method and application thereof

    CN115642305A

Cited By

  • A composite diaphragm based on solid electrolyte coating and preparation method thereof

    CN119742538A

  • A composite diaphragm based on solid electrolyte coating and preparation method thereof

    CN119742538B

  • Solid electrolyte material, electrode, battery and preparation method

    CN121076226A

  • Solid-state electrolyte material, electrode, battery, and method of preparation

    CN121076226B

  • Preparation method of low-cost and easy-to-process oxide solid electrolyte

    CN121342507A